Participation of Women in the United States Congress: 1917-2011 - Chojnacka, Magdalena (Acta Agraria Debreceniensis, 2012)
The last decades have carried changes in the legal and social position of women bearing enfranchisement, a new approach to women’s education, and their increased participation in the job market. This article outlines the historical participation of women on the political scene of the United States between the years of 1917-2011 including an analysis of the situation in the individual states. Furthermore, it analyses what types of positions have been held by women in the American Government Administration including the most prestigious ones of the Speaker and the Secretary of State. It also introduces Hilary Rodham Clinton, the first woman ever to run in the presidential elections 2008. This analysis reveals that women are still underrepresented in the federal-level positions which makes it difficult for them to influence the quality of the lawmaking and results in a difficulty to promote such decisions that are important for the women themselves.